Отчет о научных исследованиях, поддерживаемых Королевским обществом защиты птиц Великобритании в заповеднике Койтендаг (Восточный Туркменистан) - Джефф Уэлч (Pensoft Publishers, 2019)
All of the work in Turkmenistan detailed in this report was carried out under the Memorandum of Understanding between the Ministry of Agriculture and Environment Protection of Turkmenistan and the Royal Society for Protection of Birds, within the Project on "Improvement of the status of birds and other biodiversity in Turkmenistan".